Deciphering the Effect of Hyaluronic AcidCollagen Hydrogel for Pain Relief and Tissue Hydration in a Rat Model of Intervertebral Disc Degeneration - Rusydi Mohd Razak; Nur Arina Amira Harizal; Mohammad Ali Zuhdi Azman; Najwa Syakirah Mohd Redzuan; Raed H. Ogaili; Ahmad Hafiz Kamarrudin; Muhammad Fakhrullah Mohamad Azmi; Nur Aqilah Kamaruddin; Aminatul Saadiah Abdul Jamil; Sabarul Afian Mokhtar; Isma Liza Mohd Isa (MDPI Publication, 2024)
Indexed by WOS/Scopus/ERA